Evaluation of Learning Outcome Assessment System in Health and Sports Physical Education Subject in Junior High School - Ismail Ismail; Indri Astuti; Aloysius Mering (JETL (Journal of Education, Teaching and Learning), 2018)
Research aims to find out: (1) context of learning outcome assessment system, (2) input evaluation of the results assessment system, (3) component of the assessment system implementation process, (4) product learning outcomes assessment system. This study includes evaluation research with the CIPP M\model (context, input, process, product) with a qualitative and quantitative approach and using qualitative descriptive analysis methods. Data collection techniques used are (1) questionnaires, (2) observation, (3) interviews and (4) documentation. Data analysis techniques for quantitative data are (1) editing, (2) coding, and (3) tabulating. For qualitative data are: (1) data reduction, (2) presentation of data, and (3) draw conclusions. Results of the study: (1) the target of assessing learning outcome in PJOK subjects in Ketapang Junior High School is still lacking, such as in the assessment instrument between friends, journal, projects. (2) preparation of the semester program is not prepared a special time for daily tests. In the preparation of the RPP which small teachers were still not included in the problem text, key answers, and assessment guidelines. (3) the assessment process is not in accordance with the time specified, the teacher has not optimally discussed midterm exam questions. (4) reports on the assessment of student learning outcomes include affective, cognitive and psychomotor aspects, as well as the report, contains descriptive notes that are useful for parent and a follow up in efforts to improve the learning process in general. The assessment system of learning outcomes in PJOK subjects in Ketapang Junior High School is in accordance with the 2013 curriculum assessment guidelines. In the implementation of the assessment, it is expected that the participation of principals, supervisors and relevant agencies, in order to provide technical guidance to teachers in the assessment process so that the assessment process is carried out maximum in accordance with the 2013 curriculum.